Long-term follow-up of 61 coeliac patients diagnosed in childhood: evolution toward latency is possible on a normal diet. Issue 10 (15th February 2007) - Matysiak-Budnik, Tamara; Malamut, Georgia; de Serre, Natacha Patey-Mariaud; Grosdidier, Etienne; Seguier, Sylvie; Brousse, Nicole; Caillat-Zucman, Sophie; Cerf-Bensussan, Nadine; Schmitz, Jacques; Cellier, Christophe
Abstract : Background/Aims: Whether a life-long gluten-free diet (GFD) is necessary in all children with diagnosed coeliac disease (CD) remains debated. To address this question, a retrospective analysis of the clinical and biological status of adult coeliac patients diagnosed in childhood, who remained on a normal diet after gluten challenge and were clinically silent, was carried out. Methods: Patients aged 18–65 years with CD diagnosed in childhood were included. Clinical status, gluten intake, biological parameters of malabsorption, bone mineral density, human leucocyte antigen (HLA) genotype, serological markers of CD, and histological and immunohistochemical parameters in duodenal biopsies were recorded. Results: Sixty-one patients had resumed a normal diet and were asymptomatic. Forty-eight showed different degrees of villous atrophy (silent CD), while 13 had no detectable atrophy (latent CD) on duodenal biopsies. Latent CD patients had significantly less osteopenia/osteoporosis (1/9 (11%) vs 23/33 (70%), p<0.001)), and lower T cell receptor (TCR) αβ+ intraepithelial T cell counts (38±20 vs 55±15, p<0.01) than silent CD patients. The mean age at diagnosis and first GFD was lower in latent than in silent patients (14.4±5 vs 40.1±47 months, p<0.05). Latent patients did not differ significantly from the seven control patients on a long-term GFD, except for a higher frequency of CD-specific serum antibodies. However, two latent patients relapsed clinically and histologically during subsequent follow-up. Conclusions: Long-term latency developed in about 20% of CD patients who remained symptom free after gluten reintroduction. This latency can be transient and thus a regular follow-up is mandatory. In silent patients, the increased risk of osteoporosis substantiates the need for a GFD.